Reference Range of Stomatocytes in Jakarta and Surrounding Areas - Danny Ernest Jonas Luhulima; Ago Harlim; Laurensius Aldrico Marveliano Sena; Ria Amelia; Erida Manalu (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Stomatocytes are erythrocytes characterized by a slit-like central pallor. Although they may appear in small numbers under physiological conditions, increased proportions are often associated with pathological states. Establishing population-specific reference intervals is therefore essential to avoid misinterpretation of erythrocyte morphology. This study aims to determine the reference interval for Stomatocyte counts in a healthy population from Jakarta and its surrounding areas, and to assess their relationship with routine hematological and biochemical parameters. A descriptive cross-sectional study was conducted among healthy individuals undergoing health check-ups at UKI General Hospital and East Bekasi Hospital from August 2022 to October 2024. Of 65 samples collected, 54 met the inclusion criteria. Stomatocyte counts were evaluated from peripheral blood smears by counting per 1,000 erythrocytes. Reference intervals were established using the 2.5th to 97.5th percentile method. The overall reference interval for Stomatocytes was 0 - 1.85%. Gender-specific intervals were 0 - 2.0% in men and 0 - 1.7% in women. No significant associations were observed between Stomatocyte counts and complete blood count parameters, liver function tests, or kidney function tests. In conclusion, Stomatocytes may be present at low levels in healthy individuals, with a locally derived reference interval of 0 - 1.85%. These findings highlight the importance of applying clearly defined reference intervals and considering clinical context when interpreting erythrocyte morphology to prevent overdiagnosis. Keywords: Stomatocytes, Reference Values, Erythrocyte Morphology,  Peripheral Blood Smear.